Climatic controls on phosphorus concentrations in The Loch, Loch Vale Watershed, Rocky Mountain National Park, Colorado, USA since the last glacial maximum. (November 2022) - Price, Jason R.; Szymanski, David W.; Slemmons, Krista E.H.; Eskey, Mackenzie; Johnson, Edward; Bricker, Suzanne
Abstract: The alpine–subalpine Loch Vale watershed (LVW) of Colorado, USA, has relatively high natural lithogenic P 5+ fluxes to surface waters. For 1992–2018, the largest number of stream samples with P 5+ concentrations ([P 5+ ]) above detection limits occurred in 2008, corresponding with the highest frost-cracking intensity (FCI). Therefore, relatively cold winters and warm summers with a comparatively low mean annual temperature partly influence stream [P 5+ ]. Sediment cores were collected from The Loch, an outlet lake of the LVW. Iron-, Al-, and Mn-oxide-bound phosphorus (adsorbed and authigenic phosphates; NP) serves as a proxy measurement for paleolake [P 5+ ]. The highest NP in the core occurred during the cold and dry Allerød interstade. The lowest NP concentrations in the core occurred during climatically very wet periods in the Late Pleistocene and Early Holocene. Therefore, [P 5+ ] are highest with relatively cold winters followed by relatively warm summers, relatively low mean annual temperatures, and relatively little rainfall and/or cryospheric melting. Currently the LVW is experiencing warming and melting of the permanent cryosphere with a rapidly declining FCI since 2008. This has the potential to dramatically decrease [P 5+ ] in surface water ecosystems of the LVW, reducing biological productivity, enhancing P-limitation, and increasing ecosystem reliance on aeolian P 5+ .